2021
DOI: 10.4018/978-1-7998-6776-0.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, Entrepreneurship, and Sustainability for ICT Students Towards the Post-COVID-19 Era

Abstract: The purpose of the study reported on in this chapter was to develop a structural equation model (SEM) of the drivers of innovation for information and communication technology (ICT) students. Against a background of research on entrepreneurship and sustainability towards the post-COVID-19 era, factors had previously been identified, which promoted innovation among employees. A literature review, however, also revealed issues, controversies, problems, and challenges related to the effects of knowledge sharing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In particular, we look into the individuals' data and information, highlighting the pros and cons of big data use, information fluidity, and beyond just motivating factors and implications already addressed in the literature . While three key areas of innovation, entrepreneurship, and sustainability are highlighted as potential future directions (Ngugi and Goosen, 2021), we note that individuals' data collection issues could lead to consequences that may not be necessarily fully beneficial to all. However, this trend of information use has existed for a long but has been boosted due to mobility control and measures implemented at multiple scales during this ongoing pandemic.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, we look into the individuals' data and information, highlighting the pros and cons of big data use, information fluidity, and beyond just motivating factors and implications already addressed in the literature . While three key areas of innovation, entrepreneurship, and sustainability are highlighted as potential future directions (Ngugi and Goosen, 2021), we note that individuals' data collection issues could lead to consequences that may not be necessarily fully beneficial to all. However, this trend of information use has existed for a long but has been boosted due to mobility control and measures implemented at multiple scales during this ongoing pandemic.…”
Section: Introductionmentioning
confidence: 95%
“…Opportunity exploration refers to the search for new ideas, methods or approaches to perform a task or to solve problems that are different from the usual way (Ngugi, 2021, Benitez, et al, 2018. The study by Tu, et al (2022) found that when employees have the opportunity exploration behaviour, the sustainable development of the company can be achieved or maintained and objectives can be achieved.…”
Section: Opportunity Exploration IImentioning
confidence: 99%
“…Therefore, it is important to turn this negative period into a positive one and to change public perceptions about the pandemic crisis. Entrepreneurship, therefore, becomes requisite in times of crisis as it lays out a positive perspective on the new conditions ( Ngugi and Goosen, 2021 ). Withal, young highly educated individuals are more oriented to entrepreneurial intentions (EIs) and actions than adult people with or without advanced education ( Turker and Sonmez Selcuk, 2009 ).…”
Section: Introductionmentioning
confidence: 99%